Critical socio-technical issues surrounding mobile computing - Mohamed, Norshidah; Montoro, Teddy; Ayu, Media Anugerah; Mahmud, Murni (IGI, 2016)
Description As lifestyles in personal and public spheres become more fast-paced and hectic, the need for reliable mobile technologies becomes increasingly important. Insights into the various impacts of mobile applications pave the way for future advances and developments in communication and interaction.